FILSAFAT HUMANISME ABRAHAM MASLOW DALAM PERSEPEKTIF PEMBELAJARAN BERDIFERENSIASI - Wiyoko, Tri (Jurnal Muara Pendidikan, 2024)
The philosophy of humanism in Abraham Maslow's thinking and the hierarchy of individual needs provides an educational concept that highly values ​​human development. This is very much in line with Differentiated Learning. The purpose of writing this article is to describe the concept of differentiated learning and review it from the perspective of the philosophy of humanism education. This research used the literature study method to collect literature on differentiated learning and Abraham Maslow's humanism philosophy. Furthermore, the collected references will be synthesized to provide information logically, meaningfully, and analyzed descriptively and argumentatively. The study results showed that the philosophy of humanism from Abraham Maslow's thinking is very relevant to be implemented in differentiated learning. Student needs largely determine the fulfilment of needs in differentiated learning. Student needs can be met by providing differentiation of content, processes, products, and a comfortable learning environment. Therefore, differentiated learning can realize a learning process that humanizes students by applying the hierarchy of needs.